Spectroscopic behavior of various materials in a GEO simulated environment. (December 2021) - Reyes, Jacqueline A.; Fulford, Karin W.; Plis, Elena A.; Hoffmann, Ryan C.; Murray, Vanessa J.; Cowardin, Heather M.; Cone, Darren; Ferguson, Dale C.; Bengtson, Miles T.; Shah, Jainisha R.; Engelhart, Daniel P.
Abstract: Artificial objects currently populating Earth orbital regimes can be distinguished by comparing remote observational data to that of optical measurements within the visible (VIS) and near infrared (NIR) spectral regions of materials obtained in the laboratory. Careful comparison of spectrally resolved observations with laboratory-based material irradiation experiments can provide a tool for remote diagnosis and anomaly resolution. However, the spectral signatures of many materials change as a function of exposure to radiation in geosynchronous Earth orbit (GEO). In order for remote characterization to be a viable characterization technique, the evolution of material optical properties (VIS-NIR) upon exposure to the GEO environment must be understood. To this end, we have studied the reflectance of several commonly used spacecraft materials including organic polymers, solar cell coverglasses, black thermal control paint, and carbon-carbon (C–C) matrix composite as a function of exposure to high energy electron irradiation in order to mimic the harsh environment of GEO. It was found that different classes of materials exhibit large variation in radiation stability resulting in the development of unique spectral characteristics. Highlights: Select spacecraft materials were optically measured using reflectance spectroscopy. Materials included organic polymers, solar cells, paint, metals, and composites. Measurements conducted in a geostationary Earth orbit (GEO) simulated environment. Spectral signatures of materials prior and post space weathering have been analyzed.